2019
DOI: 10.1080/00140139.2019.1577497
|View full text |Cite
|
Sign up to set email alerts
|

Medium-term effects of a two-desk sit/stand workstation on cognitive performance and workload for healthy people performing sedentary work: a secondary analysis of a randomised controlled trial

Abstract: View related articles View Crossmark data Citing articles: 3 View citing articles Medium-term effects of a two-desk sit/stand workstation on cognitive performance and workload for healthy people performing sedentary work: a secondary analysis of a randomised controlled trial

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 99 publications
(144 reference statements)
0
11
0
Order By: Relevance
“…The pain and discomfort caused by musculoskeletal disorders is often in the neck, shoulders and lower back due to the amount of time spent in a seated position 51 ) . Alternating body positioning though the use of sit-stand desks may reduce or slow the development of musculoskeletal pain associated with sedentary work 4 ) . It has also been reported that short-term and long-term pain may adversely affect cognition, particularly memory and attention 50 , 52 ) due to attentional interference 50 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pain and discomfort caused by musculoskeletal disorders is often in the neck, shoulders and lower back due to the amount of time spent in a seated position 51 ) . Alternating body positioning though the use of sit-stand desks may reduce or slow the development of musculoskeletal pain associated with sedentary work 4 ) . It has also been reported that short-term and long-term pain may adversely affect cognition, particularly memory and attention 50 , 52 ) due to attentional interference 50 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Sedentary behaviors typically involve sitting, reclining or lying (e.g., computer activities, driving a vehicle, watching television), and are associated with a metabolic expenditure score (MET) that does not exceed 1.5 MET 1,2) . Evidence has built over recent years pointing to detrimental impacts of sedentary behavior on physical health (e.g., cardiometabolic and musculoskeletal) and cognitive performance (e.g., attention and concentration) [2][3][4] . Office workers are particularly susceptible to long periods of sedentary behavior due to prolonged periods of sitting throughout the day 2,5,6) , with Australian office workers spending between 62%-82% of their working day engaged in sedentary behaviors 7) .…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence claims the existence of a bidirectional relationship between PA and mental health (Maugeri et al, 2020). Apart from deviating from the monotonous work threat, PA is claimed to have a positive effect on mental health by improving cognitive functions by regulating plausible mechanisms: glucose metabolism in brain (Wheeler et al, 2017), cortical perfusion (Carter et al, 2018) and neuroendocrine responses such as enhanced brain‐derived neurotrophic factor, dopamine agonists (Wennberg et al, 2016) and cortisol levels (Schwartz et al, 2019). Reducing sitting time through home‐based exercise or standing or climbing stairs or planned walk breaks can favourably improve physical and mental health of adults who are WFH (Ghram et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Greater technology utilisation has resulted in an increase in the sedentary nature of work and the health risks associated with it, such as diabetes and obesity (van Uffelen et al 2010). These issues have also attracted E/HF attention, although there tends to be an emphasis on individual behaviour, for example, in the introduction of alternative workstations (Buckley et al 2015;Schwartz et al 2019) or workplace exercise programmes (Commissaris et al 2016). Investigating micro issues can lead to examination of a macro perspective, as is evidenced by the consensus of ergonomists over time that the management of workplace musculoskeletal disorder is most effectively managed with a multi-factorial approach (Devereux, Vlachonikolis, and Buckle 2002;Widanarko et al 2014).…”
Section: Introductionmentioning
confidence: 99%